COVID-19 Vaccination Status and Pregnant Women’s Perceptions of Pandemic Omicron COVID-19 Wave in Indonesia (KEMAS: Jurnal Kesehatan Masyarakat, 2023)
Pregnant women are susceptible to COVID-19 infection. COVID-19 vaccination protects pregnant women. This study aims to determine their perception of COVID-19 vaccination and its relation to the Omicron Variant wave of the COVID-19 pandemic in Indonesia. This cross-sectional study took time from February to March 2022. Subjects were asked to sign an informed consent and fill out a questionnaire. Demographic data, vaccination status, and perception of the pandemic were collected and statistically analyzed. Of the 361 study subjects, 219 (60%) are vaccinated, and 142 (40%) are unvaccinated. The vaccinated pregnant women were less anxious about the COVID-19 pandemic (p0.001, OR 2.24). Pregnant women with higher education or those who work were also less anxious about the COVID-19 pandemic (p0.05; OR 1.58 and OR 1.6). Most unvaccinated subjects were afraid of the vaccine’s effects on the fetus (62%). The emergence of the Omicron variant is the most cause of anxiety (38%). The most reason for pregnant women who were not anxious is because they had received vaccination (55%). The COVID-19 vaccination can provide a sense of security for pregnant women facing the COVID-19 pandemic.